The influence of guided inquiry learning based on local wisdom and android applications on students' high-order thinking skills (HOTS) - Muhammad Zaini; Ali, Lalu Usman; Handriani, Lia Saptini; Fitriana, Iin Mahlia (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to evaluate the effects of a guided inquiry learning model, grounded in local wisdom and delivered through an Android application, on the higher-order thinking skills of students in physics education. The study employed a quasi-experimental design featuring a pretest-posttest non-equivalent control group. Participants included science students from classes XA and XB, with class XA serving as the experimental group and class XB as the control group, selected through purposive sampling. Quantitative data, comprising pretest, posttest, and N-Gain scores related to students' higher-order thinking skills, were analyzed using an independent sample t-test (α = 0.05) via SPSS 25.0 for Windows. The findings revealed a significant effect (Sig. 0.010 < 0.05). The N-gain score for the experimental group was 0.71, indicating a high level, while the control group had a score of 0.6, which falls within the moderate range. Qualitative data derived from student answer questionnaires regarding the learning process indicated an average student interest of 64.2%, categorizing it as good. The guided inquiry learning paradigm, grounded in local wisdom and facilitated by Android applications, is engaging and positively impacts students' higher-order thinking skills (HOTS).